Research Problems and Approaches in Transportation Ergonomics - Kolenc, Jurij (Promet - Traffic&Transportation, 2012)
The paper analyses the actual problems and procedures instudying ergonomics in transportation. Special emphasis is puton the specific features of the problem and the research developmentin accordance with the characteristics of the singlesub-systems and elements of the transportation system and researchapproaches.According to the structure of the development and actualproblems of the research, the following approaches have beenanalysed: psycho-physiological, systemic and technical, cybernetic,exploitation, and pedagogic, within which also the basictasks of studying ergonomics in transp01tation have been indicated.